Effects of Different Forms of Nitrogen in Dilute Sea Salt on the Germination and Growth, of Vigna unguiculata L. Walp in a Hydroponic System - Lillian Muzaki (Uganda Christian University, 2024)
Hydroponic growth systems are a convenient platform for studying whole plant physiology. Major yield loss in cowpea (Vigna unguiculata) can be attributed to biotic and abiotic stresses. A cost effective and time saving screening protocol for cowpea abiotic stresses will enhance and expedite research on cowpea by breeders thereby enhancing its production and availability to meet increasing demand and population rise. Different crops have different forms of nitrogen they prefer, different crops grow differently in salt media which has trace elements needed by plants for growth, but because of associated salinity issues, different crops show different results. In this study, the effect of different forms of nitrogen in dilute sea salt on the germination and growth Vigna unguiculata L. Walp (cowpea) in a deepwater hydroponic system was studied. Data on germination and growth was entered in MS Excel, cleaned and exported in Gensart 12, analyzed, means, standard deviation, coefficient of variation were generated. Analysis of variance (ANOVA) was calculated and significaly mean values were compared using Ducan multiple range test at 5% significancy level. Plants in nutrient solution with nitrates and free nitrogen ions in sea salt showed better results of germination and growth than crops grown in nutrient solution without sea salt and the worst results were present by nutrient solution with ammonia as a form of nitrogen in sea salt. These results indicate that addition of sea salt (10% dilution) in nutrient solutions and using nitrogen forms nitrate and free ions affect positively the germination and growth of cowpea.
Undergraduate